Borrelia burgdorferi tolerates alteration to P66 porin function in a murine infectivity model - Fierros, Christa H.; Faucillion, Marie-Line; Hahn, Beth L.; Anderson, Phillip; Bonde, Mari; Kessler, Julie R.; Surdel, Matthew C.; Crawford, Kyler S.; Gao, Yan; Zhu, Jieqing; Bergström, Sven; Coburn, Jenifer (Frontiers in Cellular and Infection Microbiology, 2025)
Borrelia burgdorferi exists in a complex enzootic life cycle requiring differential gene regulation. P66, a porin and adhesin, is upregulated and essential during mammalian infection, but is not produced or required within the tick vector. We sought to determine whether the porin function of P66 is essential for infection. Vancomycin treatment of B. burgdorferi cultures was used to screen for P66 porin function and found to generate spontaneous mutations in p66 (bb0603). Three novel, spontaneous, missense P66 mutants (G175V, T176M, and G584R) were re-created by site-directed mutagenesis in an infectious strain background and tested for infectivity in mice by ID50 experiments. Two of the three mutants retained infectivity comparable to the isogenic control, suggesting that B. burgdorferi can tolerate alteration to P66 porin function during infection. The third mutant exhibited highly attenuated infectivity and produced low levels of P66 protein. Interestingly, four isolates that were recovered for p66 sequencing from mouse tissues revealed novel secondary point mutations in genomic p66. However, these secondary mutations did not rescue P66 porin function. New structural modeling of P66 is presented and consistent with these experimental results. This is the first work to assess the contribution of P66 porin function to B. burgdorferi pathogenesis.